High diversity of medically important gastrointestinal rodent‐borne helminths in Singapore. (19th December 2017) - Mendenhall, I. H.; Ch'ng, L.; Neves, E. S.; Borthwick, S. A.; Smith, G. J. D.
Summary: Small mammals are important reservoirs of zoonotic diseases and are definitive hosts for medically important parasitic helminths. Several rodent and shrew species are peridomestic, bringing them into close contact with both humans and the intermediate hosts that maintain the transmission cycle. Here, we screened DNA extracted from large intestine tissue homogenate from 108 individuals comprised of 10 species. We detected two species known to infect humans, Dicrocoelium dendriticum and Moniliformis moniliformis . We also report the first detection of a second Angiostrongylus species in Singapore. This study demonstrates the diversity of helminths that are parasitizing the small mammals in Singapore.